Sunshine state [videorecording (DVD)] - Sayles, John, 1950-; Clapp, Gordon; Bassett, Angela; Alexander, Jane, 1939- (Sony Pictures classics., 2002)
The rumbling approach of real estate developers on a sleepy Florida island sets the leisurely paced plot in motion.